Low sodium intake ameliorates hypertension and left ventricular hypertrophy in mice with primary aldosteronism - Wang, Zitian; Zhao, Xue; Bu, Lifang; Liu, Kun; Li, Ziping; Zhang, Huaxing; Zhang, Xiaoguang; Yuan, Fang; Wang, Sheng; Guo, Zan; Shi, Luo (Frontiers in Physiology, 2023)
The goal of this paper is to elucidate the effects of sodium restriction on hypertension and left ventricular (LV) hypertrophy in a mouse model with primary aldosteronism (PA). Mice with genetic deletion of TWIK-related acid-sensitive K (TASK)-1 and TASK-3 channels (TASK−/−) were used as the animal model of PA. Parameters of the LV were assessed using echocardiography and histomorphology analysis. Untargeted metabolomics analysis was conducted to reveal the mechanisms underlying the hypertrophic changes in the TASK−/− mice. The TASK−/− adult male mice exhibited the hallmarks of PA, including hypertension, hyperaldosteronism, hypernatremia, hypokalemia, and mild acid-base balance disorders. Two weeks of low sodium intake significantly reduced the 24-h average systolic and diastolic BP in TASK−/− but not TASK+/+ mice. In addition, TASK−/− mice showed increasing LV hypertrophy with age, and 2 weeks of the low-sodium diet significantly reversed the increased BP and LV wall thickness in adult TASK−/− mice. Furthermore, a low-sodium diet beginning at 4 weeks of age protected TASK−/− mice from LV hypertrophy at 8–12 weeks of age. Untargeted metabolomics demonstrated that the disturbances in heart metabolism in the TASK−/− mice (e.g., Glutathione metabolism; biosynthesis of unsaturated fatty acids; amino sugar and nucleotide sugar metabolism; pantothenate and CoA biosynthesis; D-glutamine and D-glutamate metabolism), some of which were reversed after sodium restriction, might be involved in the development of LV hypertrophy. In conclusion, adult male TASK−/− mice exhibit spontaneous hypertension and LV hypertrophy, which are ameliorated by a low-sodium intake.